Ailadinium reticulatum gen. et sp. nov. (Dinophyceae), a New Thecate, Marine, Sand‐Dwelling Dinoflagellate from the Northern Red Sea. Issue 6 (7th November 2014) - Saburova, Maria; Chomérat, Nicolas; DeClerck, O.
<x xml:space="preserve">Abstract</x> A new photosynthetic, sand‐dwelling marine dinoflagellate, Ailadinium reticulatum gen. et sp. nov., is described from the Jordanian coast in the Gulf of Aqaba, northern Red Sea, based on detailed morphological and molecular data. A. reticulatum is a large (53–61 μm long and 38–48 μm wide), dorsoventrally compressed species, with the epitheca smaller than the hypotheca. The theca of this new species is thick and peculiarly ornamented with round to polygonal depressions forming a foveate‐reticulate thecal surface structure. The Kofoidian thecal tabulation is APC (Po, cp), 4′, 2a, 6′′, 6c, 4s, 6′′′, 1p, 1′′′′ or alternatively it can be interpreted as APC, 4′, 2a, 6′′, 6c, 4s, 6′′′, 2′′′′. The plate pattern of A. reticulatum is noticeably different from described dinoflagellate genera. Phylogenetic analyses based on the SSU and LSU rDNA genes did not show any supported affinities with currently known thecate dinoflagellates.